2011
DOI: 10.1080/00377996.2010.538758
|View full text |Cite
|
Sign up to set email alerts
|

Reading for Democracy: Preparing Middle-Grades Social Studies Teachers to Teach Critical Literacy

Abstract: The role of literacy instruction-and more specifically the ability to read critically-in democratic and Social Studies education has not been fully or explicitly explored. This gap is also strikingly evident in the reluctance of many Social Studies teachers to incorporate reading instruction into their practice. In this paper we describe our efforts to engage preservice middle grades Social Studies teachers in critical literacy practices as a first step toward more effectively and meaningfully integrating read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…However, an engaging and cultural responsive approach to learning in middle level social studies does not mean abandoning the curriculum content teachers are required to be conduits of. Critical literacy (Evans & Clark, 2015;Reidel & Draper, 2011), culturally relevant texts, simulations (DiCamillo & Gradwell, 2012;Gradwell & DiCamillo, 2013), and purposeful pedagogy (Milner, 2014) can foster culturally responsive teaching for middle level Latino learners while still meeting the demands of teaching in an era of standards-based high-stakes testing.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…However, an engaging and cultural responsive approach to learning in middle level social studies does not mean abandoning the curriculum content teachers are required to be conduits of. Critical literacy (Evans & Clark, 2015;Reidel & Draper, 2011), culturally relevant texts, simulations (DiCamillo & Gradwell, 2012;Gradwell & DiCamillo, 2013), and purposeful pedagogy (Milner, 2014) can foster culturally responsive teaching for middle level Latino learners while still meeting the demands of teaching in an era of standards-based high-stakes testing.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…While there is extensive literature and research on literacy, and ample literature promoting the amalgamation of literacy and social studies, as a whole social studies tends to be devoid of literacy instruction, regardless of the specific definition utilized for literacy (Draper et al, 2005;Moje, 1996;O'Brien and Stewart, 1990;Reehm and Long, 1996;Simonson, 1995). In part, this could be attributed to the fact that many social studies teachers still think of literacy in its most basic form (that is, reading and writing), as they are often overheard saying that they do not teach reading (Hall, 2005;Reidel and Draper, 2011b). According to Moje (2008: 98):…”
Section: Social Studies and Literacymentioning
confidence: 99%
“…As with earlier searches, this resulted in a limited number of studies. Reidel and Draper (2011) addressed the professional development of preservice middle school teachers in research context in critical literacy practices as they prepared to teach Social Studies in the hope that it would lead to meaningful technology integration. The pre-service teachers engaged in critical literacy practices each week during their Social Studies methods course where the focus was on the practice of making "text to self, text to text, and text to world connections" with the provided readings.…”
Section: Technology Integration In Classroom Practicesmentioning
confidence: 99%
“…Discussions ensued after each week's activity to evaluate how critical literacy practices could be incorporated into the classroom. Reidel and Draper (2011) concluded that mentoring graduate students in critical literacy practices with regards to digital media is essential. The study stopped short of studying graduate students as they implement what they learned which points to a gap in the literature.…”
Section: Technology Integration In Classroom Practicesmentioning
confidence: 99%